2018
DOI: 10.1155/2018/6528312
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Functional Properties, and Antioxidant Activities of Water-Soluble Proteins Extracted from Grasshoppers,Patanga succinctaandChondracris roseapbrunner

Abstract: Water-soluble proteins extracted from two species of grasshoppers, Patanga succincta (WSPP) and Chondracris roseapbrunner (WSPC), were characterized as well as their functional properties and antioxidant activities were investigated. e extraction yield, on a wet weight basis, was 7.35% and 7.46% for WSPP and WSPC, respectively. e most abundant amino acid in both proteins was glutamic acid, followed by aspartic, alanine, and leucine, in that order. e electrophoretic study revealed that proteins with MW of 29, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
56
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 50 publications
12
56
2
Order By: Relevance
“…Globally, cricket ingredients (11.86–13.32 m 2 /g) had higher EAI values compared to mealworms (3.01–6.50 m 2 /g) which could be due to the difference in the hydrophobicity of the proteins and the smaller size of cricket proteins, which would allow faster diffusion at the oil–water interface [ 23 , 57 , 89 ]. Chatsuwan et al [ 90 ] obtained EAI values ranging from 29.23 to 36.69 m 2 /g for P. succinta and C. rosea , respectively. Regardless of the insect species, the lower EAI values in our study can be attributed to the drying method used to produce commercial insect meals, which modifies protein solubility [ 19 ] and emulsifying properties [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, cricket ingredients (11.86–13.32 m 2 /g) had higher EAI values compared to mealworms (3.01–6.50 m 2 /g) which could be due to the difference in the hydrophobicity of the proteins and the smaller size of cricket proteins, which would allow faster diffusion at the oil–water interface [ 23 , 57 , 89 ]. Chatsuwan et al [ 90 ] obtained EAI values ranging from 29.23 to 36.69 m 2 /g for P. succinta and C. rosea , respectively. Regardless of the insect species, the lower EAI values in our study can be attributed to the drying method used to produce commercial insect meals, which modifies protein solubility [ 19 ] and emulsifying properties [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ESI values obtained by Hall et al [ 3 ] after 30 min for cricket hydrolysate (E/S of 0.5–3%; hydrolysis time of 30–90 min) were generally below 60%. Several studies have shown that the emulsion stability of insect proteins was generally low (21.2–45.4%) due to their very low solubility [ 63 , 85 , 90 ]. The size of proteins (or peptides) and the amino acid composition and distribution also influence the strength of the interfacial layer and therefore the emulsion stability [ 3 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Proteins and peptides are also involved in the antioxidant properties of insects [25,26,43], and depending on the species of edible insects these proteins might change the DPPH • and ABTS •+ radical scavenging activity. Such changes might be depend on the molecular weight of protein or peptide in question, as well as the amino acid composition [44]. Moreover, based on the high activity of DPPH • in terms of radical scavenging, the obtained results suggest that mealworm proteins contain amino acids or peptides that act as electron donors and can react with free radicals to transform them into more stable compounds.…”
Section: Antioxidant Propertiesmentioning
confidence: 89%
“…Incidentally, insects have great potential to become one of the most promising protein sources, owing to their ability to solve the global problem of protein production regarding nutrition, environment, and economic value [7,9]. Apart from their nutritional roles, insect proteins have various pharmacological properties, such as antioxidant activity, anticancer activity, and a protective effect against atherosclerosis [10][11][12][13]. Water-soluble proteins derived from grasshoppers have strong antioxidant activities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Korea Food & Drug Administration registered Ocs as a food in the Korean Food Standards Codex. Notably, Ocs proteins (Ocs-Ps) have been reported to enhance antioxidant, antimicrobial, and antiplatelet aggregation activities [ 10 , 14 , 17 ]. However, the immunological actions of Ocs-P, particularly on the innate and adaptive immune response, have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%